Movilidad académica, pasantía en proyectos internacionales con la empresa Kubo Architecture and Engineering S.L.P., Málaga, España (2019)
The process for the completion of the international internship was guided by the International Relations Office (ORI) which is responsible for executing the academic mobility agreement with the company KUBO Architecture & Engineering S.L.P. and generate the relevant information for the visa process before the embassy of Spain, with a continuous accompaniment throughout the procedure and case information. It is worth mentioning that the internship modality International is implemented since 2017, as a second option for degree in the Faculty of Architecture of the University of America Foundation, thus promoting the professional academy in an ecumenical way, demonstrating the intellectual abilities and skills that have been acquired throughout the career, projecting students to expand work options in the outside, through the cultural and professional enrichment given with the Work-type connections that are obtained during the internship.